2023
DOI: 10.1002/dad2.12404
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation and incident dementia: Effects of sex, APOE, and baseline cognitive status

Abstract: Introduction Despite the association of vitamin D deficiency with incident dementia, the role of supplementation is unclear. We prospectively explored associations between vitamin D supplementation and incident dementia in 12,388 dementia‐free persons from the National Alzheimer's Coordinating Center. Methods Baseline exposure to vitamin D was considered D+; no exposure prior to dementia onset was considered D−. Kaplan–Meier curves compared dementia‐free survival betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 62 publications
0
27
1
Order By: Relevance
“…Second, PTSD has been associated with low serum vitamin D, as well as with functional polymorphisms of the Gc protein that binds vitamin D and influences its levels. Vitamin D deficiency is associated with a modest but significant increase in the risk of dementia [78], as well as reductions in gray and white matter volumes [79], and there has been recent interest in vitamin D supplementation as a preventive measure against neurocognitive disorders [80]. Though both these findings require replication, they represent plausible pathways that could mediate the association between PTSD and neurodegeneration.…”
Section: Integration Of Existing Results On Biomarkers Of Neurodegene...mentioning
confidence: 99%
“…Second, PTSD has been associated with low serum vitamin D, as well as with functional polymorphisms of the Gc protein that binds vitamin D and influences its levels. Vitamin D deficiency is associated with a modest but significant increase in the risk of dementia [78], as well as reductions in gray and white matter volumes [79], and there has been recent interest in vitamin D supplementation as a preventive measure against neurocognitive disorders [80]. Though both these findings require replication, they represent plausible pathways that could mediate the association between PTSD and neurodegeneration.…”
Section: Integration Of Existing Results On Biomarkers Of Neurodegene...mentioning
confidence: 99%
“…49 Vitamin D deficiency may increase oxidative stress and inflammation, which are linked to dementia. 53 Fat-soluble vitamin D is needed for phosphorus, calcium, bone health, and immunological function. Recent research show vitamin D may be involved in dementia pathogenesis.…”
Section: Impact Of Vitamins On Dementiamentioning
confidence: 99%
“…26 Regarding dietary interventions, the LipiDiDiet trial 27 showed that the multi-nutrient combination Fortasyn Connect slowed cognitive decline in patients with prodromal AD, while a prospective cohort study in dementia-free people from the National Alzheimer Coordinating Center in Canada showed vitamin D to be a potential agent for dementia prevention, especially in APOE-ε4 non-carriers. 28 In terms of modifiable vascular risk factors, prospective analyses from 4932 Framingham Heart Study participants showed that a 15 mg/dL increase in high-density lipoprotein cholesterol was linked with a lower risk of AD dementia in early (35-50 y) (15.4%, P = 0.041) and middle (51-60 y) (17.9%, P = 0.014) adulthood; similarly, a 15 mg/dL increase in glucose measured in middle adulthood was linked with a higher risk for AD dementia (14.5%, P = 0.00029). Thus, by monitoring and managing blood glucose and cholesterol levels in early adulthood, the risk for AD dementia may be decreased.…”
Section: Nonpharmacological Interventionsmentioning
confidence: 99%
“…Regarding dietary interventions, the LipiDiDiet trial 27 showed that the multi-nutrient combination Fortasyn Connect slowed cognitive decline in patients with prodromal AD, while a prospective cohort study in dementia-free people from the National Alzheimer Coordinating Center in Canada showed vitamin D to be a potential agent for dementia prevention, especially in APOE-ε4 non-carriers 28 …”
Section: Nonpharmacological Interventionsmentioning
confidence: 99%